PENGARUH PANDEMI COVID 19 TERHADAP HARGA SAHAM PADA JAKARTA STOCK EXCHANGE COMPOSITE (JKSE) DAN BITCOIN PER RUPIAH INDONESIA - Endri Purnomo; Indri Rafiani Rahmawati; Muhammad Nur Holis (Nusantara Hasana Berdikari, 2022)
In today's technological era, humans prefer work that is instant and fast to meet their needs, one of which is investing. Bitcoin and stocks are one form of investment that has been widely used by investors since the emergence of the Covid-19 pandemic. The purpose of this study is to see how much the Covid-19 pandemic has affected bitcoin prices and stock prices on the JSE. This research is an explanatory research based on the research objectives that have been set previously to test the existing hypotheses. The results of this study indicate that the increase in the number of Covid-19 patients in Jakarta will cause the stock price of shares listed on the Jakarta stock exchange and also the price of bitcoin to decrease, causing investors to be increasingly reluctant to invest in stocks and trade their bitcoins. Investors and traders prefer to allocate their money to other sectors or things that they consider safer.